Knowledge Administration Between Information Technology and Productive Performance (Al-Mansour Journal, 2022)
Knowledge constitutes an essential element of active administration in that it represents a source of creativity and of improving productivity through relying on systems and models centring on information technology .This is designed to achieve extensive benefits from technological progress and ,later, to employ them in the processes of manufacturing and production ,a thing that demands reconsidering the institutional structure of the establishment "units of institutional works". The organic and interactive relation between knowledge and the way it is administered has to be recognised . This Kind of administrative system occupies the first rank among the requirements that reflect constant awareness of scientific and technological progress. This progress secures, in its turn ,the ability of the establishment to improve its performance and to promote its revenues . Accordingly , the opportunity for benefiting from the available capabilities has to be utilized . This attempt requires a kind of information technology and knowledge administration that facilitates taking appropriate decisions. The ultimate aim is to achieve competitive distinction and to allow the process of production to prosper, on bath national and international levels